PENGUATAN IDENTITAS MANUSIA INDONESIA DI LINGKUNGAN SEKOLAH SDN 049/IV JAMBI TIMUR - Mhd Fredy Al Fadri; Mia Yuliani Sihite; Monika Appryanty P; Muhammad Anugrah; Nadia Fitri Amalia (Lembaga Pengembangan Kinerja Dosen, 2024)
The questions that arise as problems in this research arise, namely: 1) Are there signs or symbols regarding the appreciation of the value of diversity as a reinforcement of Indonesian human identity at SDN 049/IV Jambi Timur 2) Do individuals within them maintain harmony and mutual respect for differences in the world? SDN 049/Iv Jambi Timur school and 3) Has the appreciation of Pancasila values at SDN 049/Iv Jambi Timur been implemented as an effort to strengthen Indonesian human identity? This research uses qualitative research. This method is used to examine natural objects and the researcher acts as an instrument. key. The data collection techniques used are triangulation (combination) of data and data analysis. Researchers must describe data according to reality without adding or subtracting from existing holistic data and describing it using words and language. The appreciation of Pancasila values in schools strengthens the identity of Indonesian people, carried out through experience and strengthening the profile of Pancasila students, namely having faith, being devoted to God Almighty, and having noble character, global diversity, working together, being independent, reasoning critically, and being creative when you are in school. in the school environment and in the classroom. The values, norms and ethics that have been contained in Pancasila have truly become a very complete and rounded part and can be integrated with the personality of every school member. So, it can form patterns of behavior, thought patterns and patterns of action and provide direction. The Indonesian education system is structured based on the culture of the Indonesian nation and is based on Pancasila and the 1945 Constitution as a form of embodiment of the life values of the Indonesian nation. The application or cultivation of values in every detail Pancasila must be taught so that individuals have attitudes and behavior that are in accordance with the noble character of the nation and do not deviate from Pancasila values which are in accordance with the principles of Pancasila. Character education needs to use Pancasila as the philosophical or ideological basis for its implementation. The use of Pancasila as a philosophical and ideological basis for character education will be able to provide direction to the knowledge system that will be built, the value system that will be fostered and developed, the basis for developing competencies that will reflect the Indonesian human character that will be formed, and how the Indonesian human character will be formed. will be fully implemented.